Dystrophinopathy patients with non-contiguous molecular alterations: Diagnosis and characterization of the genetic mechanisms involved - Luce, Leonela Natalia (2020)
Introduction: Dystrophinopathies are neuromuscular X-linked recessive diseases caused by DMD mutations. Molecular alterations in this gene are large deletions/duplications in 80% of cases and small mutations in the remaining. Several authors reported the occurrence of non-contiguous rearrangements within the same DMD allele, with frequencies up to 4%. The present work aims to characterize the incidence of complex rearrangements in an Argentinian dystrophinopathy cohort and unravel the causing molecular mechanisms.Materials and Methods: We analyzed 437 boys with clinical diagnosis of Dystrophinopathy. The following techniques were implemented: MLPA, WES, WGS, PCR-Sanger Sequencing, CGH Array and HUMARA assay. In 2 cases, breakpoints were precisely determined, so we performed a bioinformatic screening of microhomologies, interspersed repeats, secondary structures and recombinogenic motifs 50pb surrounding each breakpoint. Results: We detected 6 patients carrying complex rearrangements in DMD: 2 deletions-duplications, 3 non-contiguous duplications and 1 large deletion plus a 20pb insertion. These accounted for 1.4% of our cohort. In a deletion-duplication case, familial segregation and bioinformatics analysis suggested that the duplication was the first mutagenic event caused by Fork Stalling and Template Switching (FoSTeS), while the deletion occurred secondly by Non-homologous end joining. Furthermore, bioinformatic screening of the deletion plus insertion propose that the deletion was due to Microhomology-mediated end joining, while the insertion arose by FoSTeS. Conclusions: Our findings widen the understanding of the molecular events that may take place in DMD and characterize the occurrence of complex rearrangements in our dystrophinopathy cohort.This study was supported by PTC Therapeutics and University of Buenos Aires.